A new squat lobster species of the genus Munida Leach, 1820 (Crustacea: Anomura: Galatheoidea: Munididae) from hydrothermal vents on the Eastern Pacific Rise - Liu, Xinming; Li, Xinzheng; Lin, Rongcheng (Zootaxa, 2020)
A new species of the genus Munida Leach, 1820, is described and illustrated based on a single specimen from the deep-sea hydrothermal vent on the Eastern Pacific Rise. Munida alba sp. nov. closely resembles M. ampliantennulata Komai, 2011, M. watatsumin Komai, 2014. and M. magniantennulata, but differences in the morphologies of the third maxilliped, pollex of the cheliped and the third segment of the antennal peduncle readily distinguish the new species from the three relatives. The new species is the fourth of the genus occurring at the hydrothermal vent areas.